Argyrophilic nucleolar organiser region (AgNOR) staining in normal bone marrow cells. - Nikicicz, E P (1990)
Fifteen normal bone marrow aspirates were stained with the agyrophilic nucleolar organiser region (AgNOR) method. The results of the specific staining AgNORs as well as nuclear and cytoplasmic staining were analysed. A system was devised to characterise precisely the AgNORs present in the nuclei of bone marrow cells. Particular types of bone marrow cells had a characteristic AgNOR and non-AgNOR staining pattern. The bone marrow cells were identified easily and reliably with AgNOR staining and the method was especially useful for lymphocytes, plasma cells, erythroid cells, basophils/mast cells, monocytes and cells containing haemosiderin. The immature haemopoietic cells exhibited more and larger AgNORs than the more mature cells. It is concluded that AgNOR staining can be used to study bone marrow cells by providing additional information when used in conjunction with conventional stains.